2019
DOI: 10.1080/15592324.2019.1629270
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis protoplast isolation method reduces cytosolic acidification and activation of the chloroplast stress sensor SENSITIVE TO FREEZING 2

Abstract: Chloroplasts adapt to freezing and other abiotic stresses in part by modifying their membranes. One key-remodeling enzyme is SENSITIVE TO FREEZING2 (SFR2). SFR2 is unusual because it does not respond to initial cold stress or cold acclimation, instead it responds during freezing conditions in Arabidopsis. This response has been shown to be sensitive to cytosolic acidification. The unique lipid products of SFR2 have also been detected in response to non-freezing stresses, but what causes SFR2 to respond in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…This could explain why the WT protoplast sample appears to have a richer lipid composition than the fresh tissue it was prepared from, because it concentrates a certain type of cells only. Finally, a recent study demonstrated that the protoplast isolation itself could trigger the accumulation of some lipid species (Barnes et al, 2019), which could also explain why the WT protoplast sample appears to have a richer lipid composition than the WT leaf tissue sample.…”
Section: Protoplasts Can Be Used As a Predictive Tool For Plant Lipidmentioning
confidence: 99%
“…This could explain why the WT protoplast sample appears to have a richer lipid composition than the fresh tissue it was prepared from, because it concentrates a certain type of cells only. Finally, a recent study demonstrated that the protoplast isolation itself could trigger the accumulation of some lipid species (Barnes et al, 2019), which could also explain why the WT protoplast sample appears to have a richer lipid composition than the WT leaf tissue sample.…”
Section: Protoplasts Can Be Used As a Predictive Tool For Plant Lipidmentioning
confidence: 99%
“…In A. thaliana , NMCP homologs play a role in immunity (Choi et al ., 2019; Jarad et al ., 2019). AtORMs were reported to play roles in sphingolipid homeostasis and stress responses (Li et al ., 2016), and AtSFR2 is a membrane remodelling enzyme responsive to freezing conditions in A. thaliana (Barnes et al ., 2019). Accordingly, our findings may suggest a potential role of MpSYP12A in lipid homeostasis and stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…The ionic composition of a digestion solution is another important consideration: for example, adding certain ions (cell and protoplast washing solution) [77] or antioxidants, such as ascorbic acid, to the enzyme mixture has a significant positive effect on the quality of isolated protoplasts. A good example of such a strategy is the buffer composition for preventing cytosolic acidification that was recently proposed for Arabidopsis [78].…”
Section: The Protoplast Isolation Step As the Key For Reprogrammingmentioning
confidence: 99%
“…mixture has a significant positive effect on the quality of isolated protoplasts. A good example of such a strategy is the buffer composition for preventing cytosolic acidification that was recently proposed for Arabidopsis [78].…”
Section: Stages Of Mesophyll Protoplast Reprogramming and Accompanyinmentioning
confidence: 99%